Development of a molecular genetics and cell biology toolbox for the filamentous fungus Diplodia sapinea. - Anne Geertje Oostlander; Laura Brodde; Miriam von Bargen; Bernard Slippers; Yvonne Becker; Ulrike Brandt; Frank Klawonn; Christiaan Grobler; Lucas Well; Jan Stenlid; Jonas Oliva; Malin Elfstrand; et al. (PLoS ONE)
Diplodia sapinea (Fr.) Fuckel is a widespread fungal pathogen affecting conifers worldwide. Infections can lead to severe symptoms, such as shoot blight, canker, tree death, or blue stain in harvested wood, especially in Pinus species. Its impact on forest health is currently intensified, likely due to climate change, posing an increasing threat to global ecosystems and forestry. Despite extensive and successful research on this pathogen system, fundamental questions about its biology and plant-associated lifestyle remain unanswered. Addressing these questions will necessitate the development of additional experimental tools, including protocols for molecular genetics and cell biology approaches. In this study, we continue to address this need by establishing an Agrobacterium-mediated genetic transformation protocol for D. sapinea, enabling targeted mutagenesis and heterologous gene expression. We utilized this methodology to localize the histone H2B by tagging it with the fluorescent protein mCherry. Additionally, we established a time- and space-efficient laboratory-scale infection assay using two-week-old Pinus sylvestris seedlings. Integrating these tools in a proof-of-concept study enabled the visualization of D. sapinea in planta growth through the fluorescently labeled reporter strain.